Application of supported ionic liquid phase catalyst systems in the hydroformylation of olefin-containing mixtures to aldehyde mixtures with high portion of nonbranched aldehydes. - Franke, Robert; Brausch, Nicole; Fridag, Dirk; Christiansen, Andrea; Becker, Marc; Wasserscheid, Peter; Haumann, Marco; Jakuttis, Michael; Werner, Sebastian; Schönweiz, Andreas (2012)
The subject of the present invention is a catalyst with increased durability based on compn. of (a) an inert, porous substrate, (b) an ionic liq., (c) Rh, (d) a phosphorus-contg. org. ligand, (e) at least an org. amine. A further the subject of the present invention is a procedure for the hydroformylation of olefin-contg. hydrocarbon mixts. to aldehyde mixts. whereby: (a) the water content of the olefin-contg. hydrocarbon mixt. is adjusted to ≤20 ppm, (b) the content of multifunctional unsatd. compds. in the olefin-contg. hydrocarbon mixt. is adjusted continually to ≤3000 ppm, (c) the mol. ratio of org. amines to phosphorus-contg. ligands is ≥4:1; and (d) the mol. ratio of phosphorus-contg. org. ligand to Rh is ≥10:1. A typical catalyst consists of silica support, rhodium acetylacetonate dicarbonyl, bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate, 6,6'-[[3,3'-di-tert-butyl-5,5'-dimethoxy[1,1'-biphenyl]-2,2'-diyl]bis(oxy)]bis[dibenzo[d,f][1,3,2]dioxaphosphepin] and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and a typical reaction feed contains 1-butene, isobutene, cis-2-butene, trans-2-butene, n-butane, and isobutane, with the product being n-pentanal. [on SciFinder(R)]
Keywords: ionic liq rhodium phosphorus ligand amine catalyst supported hydroformylation; tertiary butyldimethoxy biphenyldiylbisoxybis dibenzodioxaphosphepin catalyst hydroformylation butene pentanal manuf; hydroformylation olefin catalyst unbranched aldehyde manuf; butene hydroformylation pentanal manuf catalyst; silica support hydroformylation catalyst butene pentanal manuf; rhodium acetylacetonatedicarbonyl catalyst hydroformylation butene pentanal manuf; ethylmethylimidazolium fluoromethanesulfonylimide catalyst hydroformylation butene pentanal manuf

Continuous Gas-Phase Hydroformylation of a Highly Diluted Technical C4 Feed using Supported Ionic Liquid Phase Catalysts - Haumann, Marco; Jakuttis, Michael; Franke, Robert; Schönweiz, Andreas; Wasserscheid, Peter (ChemCatChem, 2011)
The concept of supported ionic liquid phase (SILP) catalysis has been established in recent years by our group and others. Its application in continuous catalytic gas-phase processes provides a very attractive way to bridge the gap between homogeneous and heterogeneous catalysis. In this contribution, we extend SILP hydroformylation catalysis to reactions with a highly diluted, technical C4 feed containing 1.5 % 1-butene, 28.5 % 2-butenes, and 70 % of inert n-butane. To obtain the desired product, n-pentanal, the Rh-biphephos catalyst system was immobilized in the SILP system to allow for consecutive isomerization/hydroformylation activity. The resulting SILP catalyst material converted up to 81 % of the reactive butenes, with a residence time of 155s in the reactor. An n-pentanal selectivity greater than 92% was realized for more than 500h time-on-stream in the continuous gas-phase reaction. Post-reaction NMR studies revealed no significant loss of the phosphite ligand through ligand oxidation during the reaction.

Rhodium-Phosphite SILP Catalysis for the Highly Selective Hydroformylation of Mixed C4 Feedstocks - Jakuttis, Michael; Schönweiz, Andreas; Werner, Sebastian; Franke, Robert; Wiese, Klaus-Diether; Haumann, Marco; Wasserscheid, Peter (Angewandte Chemie International Edition, 2011)
The cat. that got the butene: Highly active and selective diphosphite ligands are applied for rhodium-catalyzed supported ionic liquid phase (SILP) hydroformylation and make it possible to form linear n-pentanal with exceptional selectivity from a mixed butene feedstock by combined isomerization and hydroformylation (see picture, vials 1–4 show typical SILP catalysts employed in this study.). The SILP catalyst is stable for more than 800h on stream.

Supported ionic liquid phase (SILP) catalyzed hydroformylation of 1-butene in a gradient-free loop reactor - Haumann, Marco; Jakuttis, Michael; Werner, Sebastian; Wasserscheid, Peter (Journal of Catalysis, 2009)
The supported ionic liquid phase (SILP) catalysis technology was applied to gas-phase hydroformylation of 1-butene using sulfoxantphos 1 modified rhodium complexes. Kinetic experiments were performed in a fixed bed reactor and compared to a gradient-free gas-phase loop reactor (Berty type). The influence of substrate concentration, temperature and syngas pressure was determined. Data from fixed bed and Berty reactor were found to be in good agreement with respect to activation energy and reaction order. Ex-situ NMR studies of fresh and used SILP catalysts confirmed that the ligand remained intact after prolonged time on stream.